A meta-analysis on pain sensitivity in self-injury - Koenig, Julian; Thayer, Julian F.; Kaess, Michael (Psychological medicine, 2016)
Individuals engaging in self-injurious behavior (SIB) frequently report absence of pain during acts of SIB. While altered pain sensitivity is discussed as a risk factor for the engagement in SIB, results have been mixed with considerable variance across reported effect sizes, in particular with respect to the effect of co-morbid psychopathology. The present meta-analysis aimed to summarize the current evidence on pain sensitivity in individuals engaging in SIB and to identify covariates of altered pain processing. Three databases were searched without restrictions. Additionally a hand search was performed and reference lists of included studies were checked for potential studies eligible for inclusion. Thirty-two studies were identified after screening 720 abstracts by two independent reviewers. Studies were included if they reported (i) an empirical investigation, in (ii) humans, including a sample of individuals engaging in (iii) SIB and a group of (iv) healthy controls, (v) receiving painful stimulation. Random-effects meta-analysis was performed on three pain-related outcomes (pain threshold, pain tolerance, pain intensity) and several population- and study-level covariates (i.e. age, sex, clinical etiology) were subjected to meta-regression. Meta-analysis revealed significant main effects associated with medium to large effect sizes for all included outcomes. Individuals engaging in SIB show greater pain threshold and tolerance and report less pain intensity compared to healthy controls. Clinical etiology and age are significant covariates of pain sensitivity in individuals engaging in SIB, such that pain threshold is further increased in borderline personality disorder compared to non-suicidal self-injury. Mechanisms underlying altered pain sensitivity are discussed.
Gesehen am 29.04.2020